Pemanfaatan Pupuk Organik Kulit Pisang Dan Azolla Terhadap Pertumbuhan Kangkung Darat Dengan Sistem Akuaponik - Maria Sastriana; Ngadiani Ngadiani (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2019)
The aim of this study was to compare the organic fertilizer of azolla pinnata and banana peel and a combination of azolla pinnata and banana peel with the same concentration of 800 ppm to the weight of harvest and the chlorophyll content of ground spinach (Ipomoea reptans Poir.). The experiment was carried out experimentally using a completely randomized design with control treatment, 800 ppm azolla pinnata, 800 ppm banana skin and a combination of azolla pinnata and banana peels 800 ppm which were repeated 6 times each. The application was carried out by pouring 800 ppm of azolla pinnata, 800 ppm of banana peel and a combination of azolla pinnata and 800 ppm banana peel on each gutter. The results showed that azolla pinnata and banana peel nutrition had a significant effect (P <0.05) on harvest weight and chlorophyll content of ground spinach plants (Ipomoea reptans Poir.). Nutrition azolla pinnata and banana peel with a concentration of 800 ppm can increase the weight of the land spinach (Ipomoea reptans Poir.) Which has the highest average. In testing the chlorophyll content, the results of chlorophyll a content, chlorophyll b content and the highest total chlorophyll content was found in azolla pinnata 800 ppm nutrition. The results of this study concluded that 800 ppm azolla pinnata, 800 ppm banana peel and 800 ppm combination of azolla pinnata and banana peel in the growth of ground spinach plants (Ipomoea reptans Poir.) Were effective to increase harvest weight and increase chlorophyll content of land spinach (Ipomoea reptans Poir.) Namely chlorophyll a, chlorophyll b and total chlorophyll of land spinach plants (Ipomoea reptans Poir.). Keywords: ground kale, azolla pinnata, banana peel, harvest weight, test of chlorophyll content, chlorophyll a, chlorophyll b, total chlorophyll.